2007
DOI: 10.7863/jum.2007.26.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Thyroid Elastography Using Carotid Artery Pulsation

Abstract: Objective. The purpose of this study was to evaluate the feasibility of ultrasound thyroid elastography using carotid artery pulsation as the compression source and its potential for differential diagnosis of thyroid nodules. Methods. Baseband sonographic data were acquired for 16 thyroid nodules from 12 patients. The natural pulsation of the carotid artery was used as the compression source, and thyroid strain was estimated offline. For quantitative assessment of thyroid tissue stiffness, a new metric called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 19 publications
1
89
1
Order By: Relevance
“…Numerous studies are being conducted on the use of this method for the assessment of other organs, superficial and deep [11e17]. Elastographic characterization of thyroid nodules seems to be particularly useful in clinical practice, since conventional sonography provides very little information on the benign or malignant nature of these lesions [5,11,13]. Use of this technique for studying other structures in the neck (lymph nodes, salivary glands) has not been extensively studies, and additional data based on the analysis of larger series are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies are being conducted on the use of this method for the assessment of other organs, superficial and deep [11e17]. Elastographic characterization of thyroid nodules seems to be particularly useful in clinical practice, since conventional sonography provides very little information on the benign or malignant nature of these lesions [5,11,13]. Use of this technique for studying other structures in the neck (lymph nodes, salivary glands) has not been extensively studies, and additional data based on the analysis of larger series are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Lyshchik et al [1] obtained promising results with an experimental technique and equipment, which were highly interesting within a research context, but the approach they used is too complex and time-consuming for routine use in clinical practice. In contrast, Bae et al [11] have proposed an alternative to the widely used approach that involves manual compression. They showed that carotid artery pulsation can be exploited as a source of compressive stress on thyroid tissues.…”
Section: Clinical Applications Thyroidmentioning
confidence: 99%
“…The TSI or papillary carcinoma was higher comparing with benign nodular goiter, indicating that papillary carcinoma is stiffer than a benign nodular goiter [48].…”
Section: Papillary Thyroid Carcinoma (Ptc)mentioning
confidence: 99%
“…Elastography could guide the thyroid FNA biopsy to improve the sensitivity and specificity of the FNA in thyroid cancer detection and reduce the number of cases having an insufficient number of tissue samples for diagnosis [48]. …”
Section: The Value Of Biopsymentioning
confidence: 99%
“…2,3 Several research groups used the natural vascular pulsation of the carotid artery as the internal compression source and determined a nodule strain index. 4,5 Nevertheless, evaluation of nodules with this method is a laborious and time-consuming procedure not performed in real-time. Other researchers used the manual external compression method with a random phase approach on the thyroid region and scored the nodules.…”
mentioning
confidence: 99%